2020
DOI: 10.1002/cti2.1138
|View full text |Cite
|
Sign up to set email alerts
|

Screening for primary immunodeficiency diseases by next‐generation sequencing in early life

Abstract: Objective. We aimed to use next-generation sequencing (NGS) for the early diagnosis of primary immunodeficiency diseases (PIDs) and define its effects on medical management for an infant cohort in early life. Methods. A single-centre study was conducted from November 2015 to April 2018. Infants less than 3 months old with infections or abnormal white blood cell counts were enrolled in the study. Gene variants were analysed by NGS, and once a mutation was found in a PID-associated gene, the immune functions ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
0
13
0
2
Order By: Relevance
“…We previously showed that the combination of WES and CNVseq enables the diagnosis of rare neurological disorders ( Jiao et al., 2019 ). The current report indicates that NGS should also be recommended for those with undiagnosed immune abnormalities ( Sun et al., 2020 ; Zhang X. et al., 2020 ).…”
Section: Resultsmentioning
confidence: 94%
“…We previously showed that the combination of WES and CNVseq enables the diagnosis of rare neurological disorders ( Jiao et al., 2019 ). The current report indicates that NGS should also be recommended for those with undiagnosed immune abnormalities ( Sun et al., 2020 ; Zhang X. et al., 2020 ).…”
Section: Resultsmentioning
confidence: 94%
“…With the continued advancement of molecular technology, genome sequencing is becoming more common [ 37 ]. The resulting increasing numbers of medically actionable genotypes are driving the concept of “personalized medicine”.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting increasing numbers of medically actionable genotypes are driving the concept of “personalized medicine”. As this technology advances, rare genotypes will be identified and known genotypes will be “immunophenotypically” expanded [ 37 ]. Soon, the complete genomes of newborns could be routinely sequenced [ 38 ], offering unprecedented insight into and foresight for a variety of health conditions including those of the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…In an HLH cohort, ES provided molecular explanation for 58% patients, which would have been underestimated if only a specific HLH gene-panel had been used [64]. ES conducted in 2392 newborns with abnormal lymphocyte counts or infections yielded a PIDD diagnosis in 51 patients (2.13%) and 68.6% of these patients were cured or improved their outcomes when having an early diagnosis [65].…”
Section: Genetic Diagnosis and Functional Validation Of Novel Ieimentioning
confidence: 99%